Tribological behaviour of self-lubricating materials at high temperatures. (4th July 2018) - Torres, Hector; Rodríguez Ripoll, Manel; Prakash, Braham
ABSTRACT: Self-lubricating materials are becoming more widespread in fields like metal forming or power generation due to the inability to use conventional lubricants in high-temperature (HT) applications. In an effort to summarise the progress done in this field, a detailed literature review has been carried out, ranging from micron-thickness thin films to hardfacings and bulk materials, and classified by the reported solid lubricants. Moreover, the most-cited deposition techniques have been reviewed for each lubricant class in addition to their advantages and limitations. HT friction and wear data for self-lubricating materials have also been examined in order to identify effective lubrication ranges and general trends in their tribological behaviour, which is expected to be useful for researchers interested in this field. Finally, several apparent research gaps have been described, with suggestions for new experimental work that could lead to the development of new high-temperature self-lubricating materials.